2012
DOI: 10.1007/s00339-012-6935-1
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, modulus and impedance analysis of lead-free ceramics Ba0.8La0.133Ti1−x Sn x O3 (x=0.15 and 0.2)

Abstract: Titanate barium (BaTiO 3 )-type oxide ceramics Ba 0.8 La 0.133 Ti 1−x Sn x O 3 (BLTS) (here x = 0.15 and 0.2) have been synthesized by the standard solid-state reaction method. Preliminary room temperature X-ray study confirms the formation of single-phase compounds in a rhombohedral crystal system. The electrical properties of BLTS were studied using the ac impedance spectroscopy technique over a wide range of temperature (120-320 K) in the frequency range of 40 Hz to 10 MHz. The presence of a single arc in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The increase in conductivity at high temperature may be attributed to the hopping mechanism of thermally activated charge carriers. 22 After the identification of LFP as a better cathode material for LIBs by Goodenough et al, 23 in 2001, Prosini et al reported that the addition of fine particles of carbon black during the synthesis of LiFePO 4 can greatly improve the electrochemical performance. The composite material so obtained is conductive and no additional carbon black needs to be added during the electrode preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in conductivity at high temperature may be attributed to the hopping mechanism of thermally activated charge carriers. 22 After the identification of LFP as a better cathode material for LIBs by Goodenough et al, 23 in 2001, Prosini et al reported that the addition of fine particles of carbon black during the synthesis of LiFePO 4 can greatly improve the electrochemical performance. The composite material so obtained is conductive and no additional carbon black needs to be added during the electrode preparation.…”
Section: Resultsmentioning
confidence: 99%
“…The results are calculated by Nicollian and Brews method in strong accumulation region [22]: The dielectric properties of the device are examined by dielectric spectroscopy. In dielectric spectroscopy, the complex permittivity ε * is given by [23][24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…where ε' is the real part of dielectric permittivity that is a measure of the energy stored in dielectric material and ε" is imaginary part of dielectric permittivity that is a measure of the energy dissipated in dielectric material. The complex permittivity is as following [23][24][25][26]…”
Section: Resultsmentioning
confidence: 99%
“…The dielectric spectroscopy method has been commonly used to determine the dielectric properties of MS and MIS structures in the literature [35,36]. The * is the most basic point in this method and it is defined with the formula below [33,34]:…”
Section: Resultsmentioning
confidence: 99%